2000
DOI: 10.1614/0890-037x(2000)014[0608:owoafc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Wild Oat (Avena fatua) Control with ICIA 06041

Abstract: Wild oat (Avena fatua) control often is an integral management practice in cropping systems that include cereal crops. Experiments were conducted at two locations in Saskatchewan (Saskatoon and Scott), Canada, from 1994 to 1997 to determine the influence of ICIA 0604 rate (50, 100, 150, and 200 g ai/ha), water volume (30, 50, and 100 L/ha), spray mixture pH (unbuffered, close to pH 7.0; reduced, pH 4.0), late morning and evening application times, and sodium bicarbonate concentration of water source (Saskatoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The results confirm those of previous studies where reducing graminicide rates below those recommended sometimes resulted in reduced wheat yields or economic returns (O'Donovan et al, 2003a, 2003b). Other studies in wheat have reported variable results with reduced herbicide rates in terms of maintaining yields and improving economic returns (Spandl et al, 1997; Stevenson et al, 2000; Stougaard et al, 1997). In general, reduced herbicide rates performed better at relatively low wild oat densities in both barley (Belles et al, 2000; Wille et al, 1998) and wheat (Holm et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The results confirm those of previous studies where reducing graminicide rates below those recommended sometimes resulted in reduced wheat yields or economic returns (O'Donovan et al, 2003a, 2003b). Other studies in wheat have reported variable results with reduced herbicide rates in terms of maintaining yields and improving economic returns (Spandl et al, 1997; Stevenson et al, 2000; Stougaard et al, 1997). In general, reduced herbicide rates performed better at relatively low wild oat densities in both barley (Belles et al, 2000; Wille et al, 1998) and wheat (Holm et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In other study, Belles et al (2000), was found out that maximum wheat yields were obtained when wild oat herbicide, tralkoxydim, was applied at 70 to 85% of the recommended rate. In contrast, reducing the herbicide dose below the recommended rate decreased bread wheat (Triticum aestivum L.) yield by 7% (Stevenson et al, 2000). On the other hand, neither grain yield nor net return was affected when relatively low rates of several graminicides were applied to either barley or wheat (Spandl et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The cultural or mechanical weed control methods are less effective for wild oat compared to chemical control, which is the most effective for wild oat management [ 58 , 59 ]. The urea family and phenoxypropionates herbicides are considered the most effective chemical control of wild oat.…”
Section: Discussionmentioning
confidence: 99%